Oxygen Therapy in Exacerbation of Interstitial Lung Disease - Aritonang, Rachel S; Fachrucha, Fanny; Elhidsi, Mia; Desianti, Ginanjar Arum (Indonesian Society of Respirology (ISR), 2024)
Interstitial lung diseases (ILD) are a group of diseases that involve damage in the interstitial tissue, causing diffusion disorders which ultimately lead to hypoxemia. One of the conditions that aggravate hypoxemia in ILD patients is acute exacerbation. Acute exacerbation is a condition of deterioration of ILD that can occur in less than 1 month. During an acute exacerbation, there will be a worsening of the HRCT pattern with increased ground glass opacities and a worsening of the clinical picture including hypoxemia. Acute exacerbations are closely related to increased mortality rates. Oxygen administration is one of the supportive therapies that can be given to acute exacerbations. The provision of oxygen therapy is adjusted to the patient's needs using a high-flow nasal cannula, non-invasive ventilation, invasive mechanical ventilation, and extracorporeal membrane oxygenation.